2016
DOI: 10.1002/cctc.201501284
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of the Water‐Gas‐Shift Reaction by Nickel Hydroxyl Species in Partially Reduced Nickel‐Containing Phyllosilicate Catalysts

Abstract: The role of surface hydroxyl species generated by partially reduced Ni‐containing phyllosilicate structures (Ni/SiO2P) in promoting the water‐gas‐shift (WGS) reaction and methane suppression was investigated. To analyze the effect of the surface hydroxyl species, Ni/SiO2P catalysts reduced at various temperatures were employed. All the Ni/SiO2P catalysts showed enhanced catalytic performances and methane suppression compared to the conventional Ni/SiO2 catalyst. As revealed by diffuse‐reflectance infrared Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 53 publications
(141 reference statements)
5
58
0
Order By: Relevance
“…It has been reported that the crystal structure of NiPS is easily affected by the preparation and calcination environment . Previously, it was shown to be common that NiPS prepared by the same ammonia evaporation method showed different XRD patterns . In our case, from the TEM and XRD results, it can be concluded that NiO and NiPS coexist over the surface of the silica nanospheres.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…It has been reported that the crystal structure of NiPS is easily affected by the preparation and calcination environment . Previously, it was shown to be common that NiPS prepared by the same ammonia evaporation method showed different XRD patterns . In our case, from the TEM and XRD results, it can be concluded that NiO and NiPS coexist over the surface of the silica nanospheres.…”
Section: Resultssupporting
confidence: 56%
“…As the temperature increases, the intensity of the CH 4 peak decreases and that of the gas‐phase CO peaks increases clearly, which indicates the increasing conversion. −OH peaks at trueν˜ =3500–3800 cm −1 are also observed, which come from the unreduced NiPS structure . Furthermore, several peaks can be seen at trueν˜ =1400–1650 cm −1 , which are attributed commonly to carbonate species .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The methane suppression behavior for aforementioned systems is mainly due to changes in the compositions of active metals. Recently, Kawi's group has reported Ni and Ni−Cu metals supported over SiO 2 support for HT‐WGS reaction ,,. In these works the amount of methane formation is significant.…”
Section: Wgs Over Ni‐based Catalystsmentioning
confidence: 99%
“…The better WGS performance for this system is mainly attributed to the formation of Ni δ− −O v −Ti 3+ interface site, which provide the necessary dual‐active‐site required for WGS reaction. Similarly, recently our group has reported Ni‐phyllosilicate based catalysts for HT‐WGS reaction ,. In this kind of catalytic systems formation of bulk Ni particles can be minimized by embedding Ni with in the matrix of SiO 2 .…”
Section: Modifications To Ni‐based Catalysts For Methane Suppressionmentioning
confidence: 99%